Minimum System Design Of Android Based PSTN Phone - Deo Kiatama; Fransiscus Ati Halim; Arnold Aribowo (Bandar Lampung University (UBL), 2014)
PSTN phone is static. However, with the development of Android based device, wireless computer network and minimum system, it is possible to make a PSTN phone mobile. To add the mobility behavior in PSTN phone, a research to develop Android based PSTN phone is needed. Android based device will act as a remote control for the PSTN phone and can be used to make and accept a call from distance.This paper elaborates the Android based PSTN phone design. To test the system performance, two parts of testing are performed. First is testing the Android based PSTN phone remote control system and second is testing the digital voice streaming system between Android device and minimum system using UDP protocol over wireless computer network. PSTN phone remote control system is tested for its functionality while digital voice streaming system is tested for its quality by giving a sinusoidal signal to the system and comparing the input signal with output signal using oscilloscope.According to the test, Android based PSTN phone prototype is able to make a connection and disconnection of Android device (as client) with microcontroller (as server), make a connection with auto server discovery system, make a call, receive a call, and use redial and hold functions with 100% success rate in certain condition. However, it is shown that the quality of voice sent from Android phone to Arduino module is poor due to the limited size of buffer in Arduino, but on the other way around the quality of voice sent from Arduino to Android phone is good.